Effects of Crushed Glass on the Performance of Self-Compacted Concrete as a Replacement for Fine and Coarse Aggregate - Saavedra Marmanillo, Mery Herlinda (2025)
The use of recycled glass as a supplementary material in the production of self-compacted concrete offers a sustainable and effective alternative to reduce the amount of natural aggregates, promote waste recycling, and reduce environmental impact. This research aimed to analyze the effect of recycled glass in self-compacted concrete, partially replacing fine and coarse aggregate in proportions of 10%, 20%, 30%, 40%, and 50%. To evaluate its performance, several tests were performed, the most important of which are Air Content (AC), Slump Flow (SF), Passing Ability (PA) and compressive strength. The results showed differentiated behaviors between Coarse Recycled Glass (CRG) and Fine Recycled Glass (FRG). The AC in the concrete decreased as more glass was replaced. The SF was more favorable in the FRG mixes, with a more homogeneous consistency than the CRG mixes that produced segregation. As for the PA, the concrete with CRG presented greater blockages and in concrete with FRG, the lowest PA measurement was 13 mm with FRG doses of 30%. In terms of compressive strength, a significant improvement was observed in mixes with FRG percentages between 10% and 30%. In conclusion, self-compacted concrete with FRG at 30% is especially beneficial in improving compressive strength, reaching a maximum strength of 34.96 MPa. In addition, it presents less blockage, which guarantees a better flow without segregation or blockage between the structural steel rods.